Kegiatan Kelompok Kerja Kepala Madrasah Aliyah dalam Meningkatkan Kualitas Guru Pendidikan Agama Islam - Muhammad Luthful Majiid; A. Sulaeman (UM Purwokerto Press, 2022)
This study aims to determine the process, and the activities of the working group of the Head of Madrasah Aliyah in improving the quality of teachers of Islamic religious education subjects in Banyumas Regency. This type of research is descriptive qualitative. Data collection methods used in this study are observation, interviews, and documentation. Then the data analysis used by the researcher is qualitative data analysis, while the data analysis technique uses data reduction, data presentation, and data verification. With the efforts carried out such as Discourse on planning and training for teachers with the theme of making grids and questions, finalizing the cost of the end of the semester assessment, deliberations regarding the acceptance of new students, preparation of the national standard madrasah examination committee, deliberations on the national standard madrasa exam model are computer best tests, reports national standard madrasah examination committee, submission of master questions, socialization of school operational costs for national standard madrasa final exams and input for template 2, madrasa exam committee reports and reports from the education and training committee, meeting with the head of the madrasa education section, plans for the new school year and reports from the education committee and exercises, meetings with curriculum groups, curriculum development at the education unit level, meetings with madrasah operator forums, evaluation of HOTS-based learning, and so on. While the obstacles faced, there were obstacles in the Final Semester Assessment (PAS) related to grids and questions. The application used in the National Standardized Madrasah Examination (UMBN) cannot be duplicated, many shopping posts have been found that cannot be accounted for, there are Madrasah Aliyah which took part in the training rehearsal but did not send the results, the Madrasah exam was running smoothly temporarily, there were some questions that were still pending. need to be corrected on the input side of the template, there are many complaints about the online learning process in the field of Islamic Religious Education, face-to-face training activities are not permitted, the most obstacles in online learning are related to the delivery of material by teachers in the field of Islamic religious education and the evaluation process of learning outcomes.